Islamic Social Reporting of Indonesia Sharia Banks: Empirical Findings - M. Fauzan; Ananda Anugrah Nasution (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Finding and analyzing the effects of the Zakat Performance Ratio, Disclosure of Islamic Corporate Governance (Shariah Governance, General Governance), Firms Size, and Islamic Securities on Islamic Social Reporting was the goal of the study. The study employed a casual comparative methodology. Between 2017 and 2021, the population has Sharia banks registered with the Financial Service Authority. 13 samples were collected using the census (saturated) sampling method. Multiple linear regression variables were used to evaluate the data at a significance level of 5%. The study's findings demonstrated that the Zakat Performance Ratio had a favorable, considerable impact on Islamic Social Reporting. Islamic Social Reporting was negatively impacted by Islamic Corporate Governance with the indication of Sharia Governance. Islamic Corporate Governance with the indicator of General Governance had positive and significant influence on Islamic Social Reporting. Firm Size had negative and insignificant influence on Islamic Social Reporting. Islamic Securities had positive and insignificant influence on Islamic Social Reporting.